Pyogenic Odontoid Osteomyelitis with Sinus Thrombosis - Rohit Aiyer; Janice Hwang; Edward H. Yu (Case Reports in Radiology)
71/F presented with left sided headaches and neck pain with nuchal rigidity progressively worsening over 3 weeks with no other neurologic symptoms. Odontoid osteomyelitis with epidural abscess was discovered on further workup with neuroimaging. Concurrent jugular vein and transverse sinus venous thrombosis was also found and suspected to be secondary to the pyogenic odontoid osteomyelitis. Patient was treated with intravenous antibiotics for the osteomyelitis as well as intravenous heparin for the venous thrombosis. To our knowledge, this is the first case reported in literature of transverse sinus venous thrombosis secondary to odontoid osteomyelitis.